NAVI Assistant: A tool to integrate chatbots into EUD Solutions - Rubén Baena-Pérez; Iván Ruiz-Rube; José Miguel Mota; Juan Manuel Dodero (SoftwareX)
This paper introduces NAVI Assistant, a tool designed to enhance learning in an End-User Development (EUD) environment. NAVI Assistant integrates a chatbot that uses natural language understanding (NLU) and machine learning (ML) technologies for intent recognition and context management. The tool comprises components within both a browser extension and a server, ensuring efficient and secure communication. This modular architecture supports the seamless integration of various functionalities, providing users with a smooth and efficient experience. The software discussed in this work is specifically implemented for App Inventor (AI2), an environment tailored for creating mobile applications.